A evoluç\~ao da carga tributária bruta brasileira no período 1995-2007: Tamanho, composiç\~ao e especificaç\~oes econométricas agregadas - Cláudio Hamilton dos Santos; Márcio Bruno Ribeiro; Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This article discusses the dynamics of both the size and the composition of the Brazilian aggregate tax burden (BATB) in the 1995-2007 period and presents several (linear and non-linear) econometric specifications for this last variable. Our main conclusion - based both on the analysis of the dynamics of the composition of the BATB and on several of the econometric exercises presented - is that the decade-long increase of the BATB can be divided in two regimes, i.e. i) a first regime in the 1998-2003 (crisis) period in which the increase in the BATB was achieved through higher taxation of state-owned enterprises and the creation of new taxes and/or increases in existing taxes; and ii) a second regime in the 2004-2007 period in which the increase in the BATB seems to be related to an increase in firms` profits and in the degree of formalization of the overall economy (and of the labor market in particular) associated with a new (and still not quite well understood) period of economic growth.
Keywords: C22; H24; H25; 330; Steuerbelastung; Brasilien